2007
DOI: 10.1111/j.1471-4159.2007.05174.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxic damage, disrupted energy metabolism, and oxidative stress in the rat brain: antioxidant and neuroprotective effects ofl‐carnitine

Abstract: Excitotoxicity and disrupted energy metabolism are major events leading to nerve cell death in neurodegenerative disorders. These cooperative pathways share one common aspect: triggering of oxidative stress by free radical formation. In this work, we evaluated the effects of the antioxidant and energy precursor, levocarnitine (l‐CAR), on the oxidative damage and the behavioral, morphological, and neurochemical alterations produced in nerve tissue by the excitotoxin and free radical precursor, quinolinic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 47 publications
(80 reference statements)
0
67
0
Order By: Relevance
“…L-Carnitine is endogenously produced, derived from dietary sources, and is present in all tissue as a mitochondrial lipid transport carrier and energy precursor and, thus, plays important roles in diverse systemic disorders such as liver disease, kidney disease, endocrine disorders, and neurodegenerative diseases (Vaz and Wanders 2002;Silva-Adaya et al 2008;Flanagan et al 2010). D-Methionine is not endogenously present, and it has only been linked to ototoxic protection in recent years (Campbell et al 2007;Dinh and Water 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L-Carnitine is endogenously produced, derived from dietary sources, and is present in all tissue as a mitochondrial lipid transport carrier and energy precursor and, thus, plays important roles in diverse systemic disorders such as liver disease, kidney disease, endocrine disorders, and neurodegenerative diseases (Vaz and Wanders 2002;Silva-Adaya et al 2008;Flanagan et al 2010). D-Methionine is not endogenously present, and it has only been linked to ototoxic protection in recent years (Campbell et al 2007;Dinh and Water 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several antioxidants have shown the ability to protect neurons from ROS toxicity and degeneration. L-Carnitine, among a wide array of target neuroprotective agents, is of particular interest in neurons due to its role in amino acid synthesis, ATP metabolism, mitochondrial fatty acid transport, as well as its antioxidant effects (Gülçin 2006;Jones et al 2010;Nalecz et al 2004;Silva-Adaya et al 2008). Studies of murine cortical neurons have shown that L-carnitine effectively blocked neuronal apoptosis induced by increased ROS after anesthesia exposure (Zou et al 2008), attenuated the effect of methamphetamine-induced neurotoxicity, diminished the effects of other mitochondrial toxins (Virmani et al 2003), and reduced neuronal loss due to oxidative stress in animals with Huntington's disease (Vamos et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-oxidant property of L-carnitine is supported by in vitro studies demonstrating its capacity to prevent oxidant injury in various somatic cells (Silva-Adaya et al, 2008;Ribas et al, 2010). Thus, investigation of L-carnitines capacity to scavenge free radicles during IVM and its resultant effect on oocyte quality warrants investigation.…”
Section: Anti-oxidant Capacity Of L-carnitine During Ivmmentioning
confidence: 99%
“…Carnitine is responsible for transport of fatty acids across the mitochondrial membrane, and plays a role in energy generation via acetyl-coenzyme A. Excitotoxicity and disrupted energy metabolism share free radical-induced oxidative damage as a cause; ALC has shown potential to correct this. 35 The usefulness of ALC in mood disorders has been suggested by a treatment trial of 204 patients with dysthymia, where ALC was equivalent to amisulpride. 36 ALC as an adjunct to psychosocial intervention was reported to be useful in the treatment of attention deficit/hyperactivity disorder in 63 boys with fragile X syndrome.…”
Section: Acetyl-l-carnitinementioning
confidence: 99%